Penerapan Metode Agile Dalam Permodelan Sistem Informasi Inventory Barang - Nuroji Nuroji (PT. Tech Cart Press, 2023)
Problems in inventory management often arise as a significant challenge for companies. One common problem is an imbalance between inventory and customer demand, which can lead to financial losses due to overstock or lost business opportunities due to stockouts. The application of the Agile method in modeling inventory information systems is a responsive and adaptive approach to changes in a dynamic business environment. The results of the recapitulation of the 8 test criteria that have been carried out obtained the results of the number of answers from respondents, which have a value of 100% in accordance with testing the functionality of the system using blackbox testing.